Molecular characterisation of sporadic endolymphatic sac tumours and comparison to von Hippel–Lindau disease‐related tumours. (24th June 2021) - Schweizer, Leonille; Thierfelder, Felix; Thomas, Christian; Soschinski, Patrick; Kim, Hee‐Yeong; Jödicke, Ruben; Woltering, Niklas; Förster, Alexandra; Teichmann, Daniel; Siewert, Christin; Klein, Katharina; Schmid, Simone; et al.
Abstract: Aims: Although inactivation of the von Hippel–Lindau gene ( VHL ) on chromosome 3p25 is considered to be the major cause of hereditary endolymphatic sac tumours (ELSTs), the genetic background of sporadic ELST is largely unknown. The aim of this study was to determine the prevalence of VHL mutations in sporadic ELSTs and compare their characteristics to VHL‐disease‐related tumours. Methods: Genetic and epigenetic alterations were compared between 11 sporadic and 11 VHL‐disease‐related ELSTs by targeted sequencing and DNA methylation analysis. Results: VHL mutations and small deletions detected by targeted deep sequencing were identified in 9/11 sporadic ELSTs (82%). No other cancer‐related genetic pathway was altered except for TERT promoter mutations in two sporadic ELST and one VHL‐disease‐related ELST (15%). Loss of heterozygosity of chromosome 3 was found in 6/10 (60%) VHL‐disease‐related and 10/11 (91%) sporadic ELSTs resulting in biallelic VHL inactivation in 8/10 (73%) sporadic ELSTs. DNA methylation profiling did not reveal differences between sporadic and VHL‐disease‐related ELSTs but reliably distinguished ELST from morphological mimics of the cerebellopontine angle. VHL patients were significantly younger at disease onset compared to sporadic ELSTs (29 vs. 52 years, p < 0.0001, Fisher's exact test). VHL‐disease status was not associated with an increased risk of recurrence, but the presence of clear cells was found to be associated with shorter progression‐free survival ( p = 0.0002, log‐rank test). Conclusion: Biallelic inactivation of VHL is the main mechanism underlying ELSTs, but unknown mechanisms beyond VHL may rarely be involved in the pathogenesis of sporadic ELSTs. Abstract : To identify differences and to evaluate the significance of von Hippel–Lindau gene ( VHL ) alterations in sporadic endolymphatic sac tumours (ELSTs), we compared VHL‐disease‐related and sporadic ELSTs using methylation profiling, CNV analysis and next‐generation sequencing. We identified biallelic inactivation of VHL in most sporadic ELSTs as well as rare TERT promoter mutations. Our findings suggest that VHL patients are significantly younger at disease onset and a clear cell phenotype may represent a prognostic marker for both sporadic and hereditary ELSTs.